Sun Exposure: Beyond the Risks - Catarina Soares Queirós; João Pedro Freitas (Mattioli1885, 2019)
Excessive solar exposure presents well-recognized risks and side effects, solar radiation being the most important environmental factor concerning skin cancer. In the last few years, several connections between solar exposure and prevention and/or treatment of several diseases have been discussed, with studies suggesting that regular solar exposure may be beneficial for conditions such as colorectal, breast, prostate, and pancreatic cancer; non-Hodgkin lymphoma; arterial hypertension; obesity; type 2 diabetes mellitus and metabolic syndrome; nonalcoholic hepatic steatosis; multiple sclerosis; Alzheimer disease; and several psychiatric disturbances. In most cases, UV radiation's beneficial effects are mediated through vitamin D; however, studies show that in other instances other mediators are responsible for these associations, specifically nitric oxide. Moderation is therefore essential, as a strict strategy of total sun avoidance may be inadequate.